Private and open letters in the literary relationshipt between Gabriel Celaya and José García Nieto - Chicharro, Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The article studies the literary relations that the poets Gabriel Celaya and José García Nieto maintained through their private epistolary exchange, also the public through open letters seen on this occasion from the private sphere. These named poets, who never hid their personal friendship, meant in the long postwar period in Spain the resistance and political opposition from the field of letters and the cultural collaboration with the regime resulting from the civil war.